Kemampuan Berpikir Kritis Matematis Peserta Didik SMP Ditinjau dari Gaya Belajar - Ainun Fatikha Putri; Irwani Zawawi; Sarwo Edy (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to describe students’ mathematical critical thinking skills in terms of their learning styles based on the VARK model (Visual, Auditory, Reading/Writing, and Kinesthetic). The research employed a descriptive qualitative approach involving four seventh-grade students of SMP Negeri 9 Gresik, each representing one type of learning style. Data were collected through a learning style questionnaire, a mathematical critical thinking test based on Facione’s indicators, and in-depth interviews to strengthen the analysis. The results revealed that each learning style demonstrates distinct characteristics of critical thinking. Visual learners excelled in interpretation and self-regulation, auditory learners performed well in evaluation and verbal explanation, reading/writing learners showed strength in analysis and written reasoning, while kinesthetic learners were better in concrete activities but weaker in evaluation and inference. Overall, interpretation and analysis indicators were more dominant than evaluation and inference. These findings highlight the importance of implementing differentiated instruction aligned with students’ learning styles to foster optimal and comprehensive development of mathematical critical thinking skills.